Exploring empowerment in conversation: delivering video interaction guidance to families of children who are deaf or hard of hearing - Collins, Luke C. (2013)
Introduction: This work explored the concept of ‘empowerment’ in health care. A concept map of ‘empowerment’ was generated based on theories of linguistic analysis to locate aspects of empowerment in conversational data. The process of empowerment was understood within the theory of transformative learning as ‘perspective change’. A ten phase model of the transformative learning process was used to provide evidence of perspective transformation. The empowerment process was explored through the delivery of the intervention Video Interaction Guidance to 16 hearing families of pre-lingual deaf children.